2022
DOI: 10.1136/openhrt-2022-002075
|View full text |Cite
|
Sign up to set email alerts
|

Predicting arrhythmias in primary prevention heart failure patients: picking up the fragments

Abstract: Identifying patients with high-risk heart failure (HF) who would benefit from an implantable cardioverter-defibrillator (ICD) remains controversial. A potential marker for arrhythmic sudden death is fragmented QRS (fQRS). fQRS is the notching and slurring of the QRS complex in a 12-lead ECG and it indicates abnormal ventricular depolarisation and myocardial scarring and fibrosis. However, before fQRS complex can be included into selection criteria for ICD therapy, more complete reporting is required on their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…fQRS is an ECG abnormality associated with myocardial scarring and fibrosis. Consequently, its presence has been correlated in previous studies with a higher risk of ventricular arrhythmias, sudden cardiac death and all-cause mortality [ 11 , 90 , 91 , 92 , 93 , 94 ]. The relationship between spot UNa and fQRS highlights the value of spot UNa as a prognostic biomarker that can predict the risk of ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…fQRS is an ECG abnormality associated with myocardial scarring and fibrosis. Consequently, its presence has been correlated in previous studies with a higher risk of ventricular arrhythmias, sudden cardiac death and all-cause mortality [ 11 , 90 , 91 , 92 , 93 , 94 ]. The relationship between spot UNa and fQRS highlights the value of spot UNa as a prognostic biomarker that can predict the risk of ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…B Different morphologies of fragmented QRS complexes (fQRS) in the 12-lead ECG by Das et al [ 18 ] and modified fQRS Q, R and S criteria after Haukilahti et al [ 2 ]. Modified after Engstrom et al [ 20 ] …”
Section: Ventriculo-arterial Coupling As An Improved Measure Of Mecha...mentioning
confidence: 99%
“…In a recent review we showed fQRS was associated with ventricular arrhythmias and all-cause mortality in primary prevention HF patients indicated for ICD implantation [ 3 ]. fQRS is the zig-zag notching and slurring of the QRS complex that indicates myocardial scarring and fibrosis [ 2 , 20 ] (Fig. 1 B).…”
Section: Assessing Non-viable Myocardium and Arrhythmogenic Substratementioning
confidence: 99%
See 1 more Smart Citation